Compact sources and cosmological horizons in lower dimensional bootstrapped Newtonian gravity. (25th February 2021) - Casadio, Roberto; Micu, Octavian; Mureika, Jonas
Abstract: We study the bootstrapped Newtonian potential generated by a localised source in one and two spatial dimensions, and show that both cases naturally lead to finite spatial extensions of the outer vacuum. We speculate that this implies the necessary existence of a cosmological (particle) horizon associated with compact sources. In view of the possible dimensional reduction occurring in ultra-high energy processes—like scatterings at Planckian energies, the gravitational collapse of compact objects or the end-point of black hole evaporation—one can consider such lower-dimensional 'bubbles' immersed in our Universe as describing (typically Planckian size) baby Universes relevant to those dynamics.